2022
DOI: 10.15212/zoonoses-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Cryptosporidium Parasites Possess a Unique Carbohydrate-binding Protein (Malectin) that is Absent in other Apicomplexan Lineages

Abstract: Objective. Malectin is a carbohydrate-binding protein that binds Glc(2)-N-glycan and is present in animals and some alveolates. This study aimed to characterize the general molecular and biochemical features of Cryptosporidium parvum malectin (CpMal). Methods. Polyclonal antibodies were raised for detecting native CpMal by western blotting and immunofluorescence assays. Recombinant CpMal and human malectin (HsMal) were produced, and their binding activities to amylose and the host cell surface were compared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, gastric Cryptosporidium lacks any terminal glucoses or mannoses but possesses malectin, indicating that Cryptosporidium malectin plays a function that differs from humans and animals. This notion is supported by a recent study that showed difference in binding properties between human and Cryptosporidium malectins ( Wu et al, 2022 ), although the exact binding partner remains to be elucidated.…”
Section: Implication On the Parasite Biologymentioning
confidence: 72%
See 1 more Smart Citation
“…However, gastric Cryptosporidium lacks any terminal glucoses or mannoses but possesses malectin, indicating that Cryptosporidium malectin plays a function that differs from humans and animals. This notion is supported by a recent study that showed difference in binding properties between human and Cryptosporidium malectins ( Wu et al, 2022 ), although the exact binding partner remains to be elucidated.…”
Section: Implication On the Parasite Biologymentioning
confidence: 72%
“…Another interesting feature is the presence of malectin in Cryptosporidium (cgd6_110 and orthologs), but absent in other apicomplexan lineages ( Wu et al, 2022 ). Malectin in humans and animals binds to Glc 2 Man 9 GlcNAc 2 N -glycan after the trimming of the terminal glucose from Glc 3 Man 9 GlcNAc 2 to facilitate the recruitment of glucosidase II ( Schallus et al, 2008 ; Schallus et al, 2010 ; Galli et al, 2011 ; Takeda et al, 2014 ).…”
Section: Implication On the Parasite Biologymentioning
confidence: 99%